Effect of supplementation of beef cattle with different protein levels and degradation rates during transition from the dry to rainy season - Fernandes, Rodolfo Maciel [UNESP]; Almeida, Chafic Mustafe de; Carvalho, Bruna Caldas; Alves Neto, Joao Alexandrino [UNESP]; Costa Mota, Veronica Aparecida [UNESP]; Resende, Flavio Dutra de [UNESP]; Siqueira, Gustavo Rezende [UNESP] (Springer, 2016)
The objective of this study was to evaluate the effect of increasing the supply of protein with different degradation rates on the performance and metabolism of growing Nellore cattle reared on Brachiaria brizantha cv. Marandu pasture during the transition period from the dry to rainy season. The experiment was installed on an area of 34 ha, divided into 12 paddocks with an average area of 2.85 ha. In the performance evaluation were utilized 72 recently weaned, non-castrated Nellore cattle with an initial body weight (BW) of 199 kg (SEM=16). The following supplements were used: energy protein supplement containing 25 % crude protein (CP) (C-25) and energy protein supplements containing 40 % CP with one third highly degradable CP and two thirds poorly degradable CP (40-1/3NPN), one half highly degradable CP and one half poorly degradable CP (40-1/2NPN), and two thirds highly degradable CP and one third poorly degradable CP (40-2/3NPN). Higher protein degradation rates reduced supplement intake (P<0.01). In the first period, animals consuming supplement 40-1/3NPN exhibited higher average daily gain (ADG) (0.30 kg/day), similar to that of animals receiving supplement 40- 1/2NPN (P=0.04). In the second period, supplement 40-2/3NPN resulted in lower ADG (0.19 kg/day less than the other supplements). There was no effect of supplement on animal performance in the third period (P>0.10), when ADG was 0.56 kg/day. In conclusion, the response to supplementation is associated with interactions with characteristics of the forage canopy. Supplementation with a true protein source will be beneficial only during the early stage of the dry-rainy season transition period.
Keywords: Protein levels; Supplementation; Protein degradation rates; Dry-rainy season transition